Clinical Decision Support and Optional Point of Care Testing of Renal Function for Safe Use of Antibiotics in Elderly Patients: A Retrospective Study in Community Pharmacy Practice - Heringa, Mette (Drugs Aging, 2017)
OBJECTIVE: The aim was to investigate the management of drug therapy alerts on safe use of antibiotics in elderly patients with (potential) renal impairment and the contribution of optional creatinine point of care testing (PoCT) in community pharmacy practice. METHODS: Community pharmacists used a clinical decision support system (CDSS) for seven antibiotics. Alerts were generated during prescription processing in the case of previously registered renal impairment and when no information on renal function was available for patients aged 70 and over. Pharmacists could perform PoCT when renal function could not be retrieved from other health care professionals. Actions were registered in the CDSS. A retrospective descriptive analysis of alert management, performed PoCT and medication dispensing histories was performed. RESULTS: A total of 351 pharmacists registered the management of 88,391 alerts for 64,763 patients. For 68,721 alerts (77.7%), the pharmacist retrieved a renal function above the threshold for intervention. 1.7% of the alerts (n = 1532) led to a prescription modification because of renal impairment; in 3.0% of the alerts (n = 2631), the patient had renal impairment, but the pharmacist judged that no intervention was needed. Pharmacists performed 1988 PoCTs (2.2% of the alerts), which led to 15 prescription modifications (0.8% of the PoCT). CONCLUSION: Community pharmacists performed CDSS-based interventions to prevent potentially inappropriate (dosing of) antibiotics in elderly patients with renal impairment. Pharmacists were well able to retrieve information on renal function, using PoCT in a limited number of cases. The intervention rate could be greatly increased by better registration of information on renal function. Performing PoCT seems especially worthwhile in the highest age groups.